2017
DOI: 10.1002/joc.5122
|View full text |Cite
|
Sign up to set email alerts
|

Trend and periodicity of drought over Ethiopia

Abstract: We analyse rainfall extreme events in Ethiopia from 1979 to 2014 using the standardized precipitation index (SPI) and the Palmer drought severity index (PDSI) derived from both station and satellite‐based observation data sets. Causal mechanisms of extreme events are also discussed. Trend principal component (TPC), regression, wavelet and composite analyses are used to investigate the trend, frequency and inter/intra‐annual variability of extreme events (dryness/wetness of rainfall) over Ethiopia. All methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 55 publications
(190 reference statements)
4
58
0
Order By: Relevance
“…A study by Viste et al [34] reported that even through the degree of drying varies spatially, all the studied areas experienced drought at annual scales in Ethiopia. Zeleke et al [35] documented that south and southwestern regions of Ethiopia have experienced drying, while the central mountainous, north, and northwestern regions had no observed long-term trends. Recently, Worku et al [36] reported a warming trend in extreme temperature indices while an increase in rainfall extreme events in Jemma Subbasin, Upper Blue Nile Basin.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Viste et al [34] reported that even through the degree of drying varies spatially, all the studied areas experienced drought at annual scales in Ethiopia. Zeleke et al [35] documented that south and southwestern regions of Ethiopia have experienced drying, while the central mountainous, north, and northwestern regions had no observed long-term trends. Recently, Worku et al [36] reported a warming trend in extreme temperature indices while an increase in rainfall extreme events in Jemma Subbasin, Upper Blue Nile Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Drought-event is defined as a condition on land described by deficiency of water that falls below threshold level or normal average values for a certain period of time [18], [23], [24]. The deficiency of water has significant impact on surface and ground water resources [19].…”
Section: Introductionmentioning
confidence: 99%
“…Its reliability is also likely to be higher in warm climates (such as Ethiopia), where the hydrology is not affected by spring snowmelt. PDSI has also been used widely to characterize agricultural droughts [13,52,53]. Studies have shown that PDSI correlates strongly with SPI values computed using higher accumulations [54,55].…”
Section: Selection Of Meteorological and Agricultural Drought Indicatorsmentioning
confidence: 99%